A study on the effectiveness of chlorhexidine 0.2% solution on toothbrush decontamination - R Mazaheri; N Nourbakhsh; A Talebi; M Sadeghian (Isfahan University of Medical Sciences, 2010)
Introduction: Tooth brushing is a common oral health habit worldwide. Therefore hygiene of toothbrushes can play an effective role in maintaining oral health. Several factors can affect microbial contamination of toothbrushes. The aim of this study was to investigate the effectiveness of chlorhexidine 0.2% solution on toothbrush decontamination.Materials and Methods: In this experimental study, a total of 84 sterile, similar toothbrushes were given to 42 individuals in two seperate sessions. In the first session, subjects washed their brushes in the usual way after brushing their teeth. In the second session, the brushes were put in a solution of chlorhexidine 0.2% following their application by the subjects. At the end of each session, toothbrush heads were detached under sterile conditions and were put in the phosphated buffer solution (PBS) before being sent to the laboratory for microbial culture. The collected data were analyzed using Wilcoxon test with a confidence rate 0.95.Results: There was a statistically significant difference in bacterial contamination on toothbrush heads between the two sessions (P value = 0.009). In the first session (simple rinsing) 21.4% of toothbrushes were contaminated while in the second session (using chlorhexidine 0.2%) only 2.4% of samples were contaminated.Conclusion: The results of this study revealed that chlorhexidine 0.2% reduces bacterial contamination on toothbrushes. This solution is easily available and is also helpful for other oral purposes. Key words: Toothbrush, Bacterial contamination, Chlorhexidine, Colony count.